2010
DOI: 10.1016/j.nucmedbio.2009.10.007
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution imaging of brain 5-HT1B receptors in the rhesus monkey using [11C]P943

Abstract: The serotonin 5-HT1B receptors regulate the release of serotonin and are involved in various disease states, including depression and schizophrenia. The goal of the study was to evaluate a high affinity and high selectivity antagonist, [11C]P943, as a PET tracer for imaging the 5-HT1B receptor. [11C]P943 was synthesized via N-methylation of the precursor with [11C]methyl iodide or [11C]methyl triflate using automated modules. The average radiochemical yield was approx. 10% with radiochemical purity of >99% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…at end of synthesis was 24.6 ± 14.3 MBq/nmol (n = 14). Synthesis of [ 11 C]carfentanil was carried out with an AutoLoop (Bioscan, Washington,DC, USA), in a procedure similar to that used for the synthesis of [ 11 C]P943 (20). In brief, a solution of 0.5–1.0 mg of desmethyl carfentanil precursor in 80–90 μL of anhydrous DMSO and 2.5 μL of 1N CsOH in MeOH was loaded unto a stainless steel loop and reacted with [ 11 C]MeOTf for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…at end of synthesis was 24.6 ± 14.3 MBq/nmol (n = 14). Synthesis of [ 11 C]carfentanil was carried out with an AutoLoop (Bioscan, Washington,DC, USA), in a procedure similar to that used for the synthesis of [ 11 C]P943 (20). In brief, a solution of 0.5–1.0 mg of desmethyl carfentanil precursor in 80–90 μL of anhydrous DMSO and 2.5 μL of 1N CsOH in MeOH was loaded unto a stainless steel loop and reacted with [ 11 C]MeOTf for 5 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[ 11 C]P943 (R-1-[4-(2-methoxy-isopropyl)-phenyl]-3-[2-(4-methylpiperazin-1-yl)benzyl]-pyrrolidin-2-one) binds with high affinity to the 5-HT 1B receptors (Gallezot et al, 2010;Nabulsi et al, 2010). [ 11 C]P943 was prepared at the Department of Diagnostic Radiology, Yale University, New Haven.…”
Section: Radiosynthesis and Data Acquisitionmentioning
confidence: 99%
“…The PET scans were acquired for 120 min on an HRRT PET scanner (207 slices, resolution less than 3 mm full-width at half maximum in 3D acquisition mode). PET image acquisition and image reconstruction were performed as described previously (Gallezot et al, 2010;Nabulsi et al, 2010).…”
Section: Radiosynthesis and Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective 5-HT 1B antagonists such as (R)-N- [5-methyl-8-(4-methylpiperazin-1-yl)-1,2,3,4-tetrahydro-2-naphthyl]-4-morpholinobenzamide (AR-A000002) (Hudzik et al, 2003) and 1-[6-(cis-3,5-dimethylpiperazin-1-yl)-2,3-dihydro-5-methoxyindol-1-yl]-1-[2Ј-methyl-4Ј-(5-methyl-1,2,4-oxadiazol-3-yl)biphenyl-4-yl]methanone hydrochloride (SB-616234-A) (Dawson et al, 2006) have been shown to elevate serotonergic neurotransmission in vivo and exhibit effects indicative of antidepressant and anxiolytic properties in animals. The discovery of selective, high-affinity 5-HT 1B compounds made it possible to develop 5-HT 1B -specific ligands for positron emission tomography (PET) to obtain noninvasive quantification of specific binding to the receptor in brain (Pierson et al, 2008;Nabulsi et al, 2010). These tools can provide an understanding of the level of receptor occupancy required for minimal and maximal efficacy and the margin to on-target side effects that is critical for formulating a testable translational pharmacology hypothesis for early human testing.…”
Section: Introductionmentioning
confidence: 99%